A profile of the speech therapy and audiology clientele at a tertiary hospital in the Western Cape - Overett, Wendy (Division of Communication Sciences and Disorders, 2017)
It became evident in the light of proposed changes in the healthcare system in South Africa that there was little descriptive client data with regard to Speech Therapy and Audiology Services in South Africa to support proactive service planning. This study therefore aimed to describe trends in the demographic, diagnostic, and attendance variables of first-time clients who had attended the Speech Therapy and Audiology out-patient department (OPD) at a tertiary hospital in the Western Cape over a five-year period (1999-2003). A longitudinal, retrolective, descriptive survey was conducted. Records were reviewed for a sample of the population of all new clients who had attended the Speech Therapy and Audiology OPD in the five-year time frame. Data was collected using a form designed for this purpose. The data was coded and then analysed descriptively. It was found that the highest percentages of subjects attended for a hearing loss or voice disorder. The ENT department at the study hospital made the highest percentage of referrals to the Speech Therapy and Audiology Department. This was followed by referrals from the education sector. The age profile showed the highest percentage of subjects to be in the age category of 7-12 years. Similar percentages of male and female subjects were found. English was the language that a client was most likely to speak. Geographically the highest percentage of subjects attending were from the Klipfontein region, followed by the Central area. Attendance data showed that just over 70 % of subjects attended within a three-month period or attended no more than two appointments. Percentage of appointments attended decreased with increasing numbers of booked appointments. Implications of this research include issues around record keeping and service delivery. The results of this study cannot be generalized to all Speech Therapy and Audiology services in South Africa. However, the data may serve as a guide for planning services. Further research addressing service delivery issues is needed with the field of Speech Therapy and Audiology.